Conservative Ideology in the Making - Denes, Iván Zoltán (Book collections on Project MUSE., 2009)
The inheritance of the east-European autocratic system frozen up by the communist state was thawed after the regime change, the constitutional revolution, and its components began to be reactivated. "Liberal" and "conservative" have become stigmas in many parts of the world, in line with fascist, reactionary, rightist, bourgeois etc. The attempts to find historic predecessors did not favor an objective approach. There are no serious unbiased syntheses; the political poles of the constitutional revolution and the ensuing period have been described in terms of different conspiracy theories. Denes establishes distance from the enemy images and their political idioms current in today's eastern Europe. Provides in depth exploration and analysis required for the portrayal of specific features of conservatism, its strategic vision, conceptual system, argumentation, assessment criteria and values. Price's memoir weaves complicated strands-his Viennese origins, campaigns to distribute Jewish refugees away from New York City, the special qualities of Midwestern Ohio life in the 1950s-and the contrasting patterns of adjustment by different generations in his family in the American landscape. As he traces the particular path of his own life, Price reveals a more universal story of adjustment, and the relationship between a marginal community and the drama of American citizenship.